Mata Guru Roha Sisean: Berpikir Kritis dalam Mengambil Keputusan Berdasarkan Ungkapan Batak Toba dan Kristiani - Diana Martiani Situmeang; Agnes Novianti permata sari Hutahaean (Mahesa Research Center, 2021)
This article aims to develop a leraning media design for the Airlangga Museum digital catalog which is packaged in an application that can be accessed via a smartphone offline. This learning media contains material from the relics of the Hindu-Buddhist kingdom in Airlagga Museum. The making of the instructional media design is based on the analysis of problems and potentials in class X MIPA 3 SMAN 1 Plosoklaten Kediri. Based on the problem analysis, its shows that students interest in learning during online learning is low and the lack of use of innovative media is able to attract students interest in learning history. This is evidenced by the low student participation in the history learning. Design media uses the ADDIE development model which consists of five stages, namely: analysis, design, development,evaluation and implementation. The result of this learning media desing is in the form of a digital catalog equipped with a menu feature containing material in from of photos and descriptions of any relics in the Airlangga Museum. In addition, there is a quiz as an evalustion. The digital catalog of Museum Airlangga is more effective and efficient in being used as a learning medium during the pandemic because it allows students to learn relics from the Hindu-Buddhist era in Airllangga Museum without having to visit the museum.